2024
DOI: 10.3390/ijms25042335
|View full text |Cite
|
Sign up to set email alerts
|

The Thiol Group Reactivity and the Antioxidant Property of Human Serum Albumin Are Controlled by the Joint Action of Fatty Acids and Glucose Binding

Tamara Uzelac,
Katarina Smiljanić,
Marija Takić
et al.

Abstract: The binding of ubiquitous serum ligands (free fatty acids) to human serum albumin (HSA) or its glycation can affect thiol group reactivity, thus influencing its antioxidant activity. The effects of stearic acid (SA) and glucose binding on HSA structural changes and thiol group content and reactivity were monitored by fluoroscopy and the Ellman method during a 14-day incubation in molar ratios to HSA that mimic pathophysiological conditions. Upon incubation with 5 mM glucose, HSA glycation was the same as HSA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Although the obtained mean value of total proteins was low (65.5 ± 3.5 g/L) before the first race, the mean value of HSA (39.8 ± 3.6 g/L) was in the normal reference range (35-55 g/L). Because HSA is the most abundant protein in the serum (60% of total serum proteins), only one third of the total HSA content is found in the intravascular department and has a half-life of 20 days [53][54][55]; its loss by proteinuria, caused by repetitive PA, is less evident but still present (mean value 39.8 g/L was closer to the low reference value 35 g/L). According to these results, it can be concluded that repetitive PAinduced proteinuria and inadequate protein intake by recreational runners could lead to the decrease of total serum proteins, including both HSA and non-albumin proteins with low MW, such as alpha-1 antitrypsin, thyroxine-binding globulin and transcortin.…”
Section: Discussionmentioning
confidence: 72%
“…Although the obtained mean value of total proteins was low (65.5 ± 3.5 g/L) before the first race, the mean value of HSA (39.8 ± 3.6 g/L) was in the normal reference range (35-55 g/L). Because HSA is the most abundant protein in the serum (60% of total serum proteins), only one third of the total HSA content is found in the intravascular department and has a half-life of 20 days [53][54][55]; its loss by proteinuria, caused by repetitive PA, is less evident but still present (mean value 39.8 g/L was closer to the low reference value 35 g/L). According to these results, it can be concluded that repetitive PAinduced proteinuria and inadequate protein intake by recreational runners could lead to the decrease of total serum proteins, including both HSA and non-albumin proteins with low MW, such as alpha-1 antitrypsin, thyroxine-binding globulin and transcortin.…”
Section: Discussionmentioning
confidence: 72%